Irish Private Bill Legislation: a tribunal - Samuels, Arthur W. (Statistical and Social Inquiry Society of Ireland, 1899)
The demands which the Irish Local Government Bill made upon the time of Parliament last session rendered it impossible to expect that the Government could introduce the bill for the reform of Irish Private Bill Legislation, which was mentioned in the Queen's Speech for the year 1897. This reform has been advocated by the Irish Press of all politics, and has been constantly and urgently demanded for now nearly half a century by the Irish public. It is one of the most crying of our needs. The industrial progress of Ireland has been blasted by the present system. Municipal improvement has been retarded and prevented. Thousands and thousands of pounds that might have been expended on sanitation, or the beautifying and improving of cities and towns, have been wasted by this deplorable and preventible expenditure.
Read Tuesday, 22nd November, 1898
Keywords: Private Bill Legislation; Legislative reform; 314.15